Aminalon quantitative determination in drug dosage forms by spectrophotometric method - Portna, K. P.; Vasyuk, S. O.; Васюк, Світлана Олександрівна; Портна, Катерина Павлівна (India : New Delhi, 2014)
A new spectrophotometric method for the quantitative determination of aminalon in pharmaceutical formulations has been developed. This method is based on the measurement of aqueous aminalon solutions absorption at 470 nm. The proposed method is actual according to the validation requirements of Ukrainian Pharmacopeia. According to the experimental data, the technique can be correctly reproduced and it is suitable for using in the laboratories of the State Inspection for Quality Control of Medicines and QCD of the chemicopharmaceutical enterprises.
Keywords: aminalon; quantitative determination; spectrophotometric method; drug dosage forms